Comparison of the effectiveness of family resilience training, with cognitive-spiritual hope training, on family resilience in caregivers of kidney patients undergoing hemodialysis - Farhadi, Abdolhossein; Manshaee, Gholamreza; Yousefi, Zahra (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This research examines the capacity of resilience in the caregivers of kidney patients, and the impact of the care process on it. The purpose of this study was to compare the effectiveness of family resilience training with cognitive-spiritual hope training on family resilience in caregivers of kidney patients undergoing hemodialysis. Method: The research method was an experimental type with two experimental and control groups with the present pre-test and post-test design, a quantitative one with a control group and a 45-day follow-up, and the statistical population consists of all caregivers of kidney patients undergoing hemodialysis. Isfahan city in 2020-21, in this research, 60 caregivers were selected through available sampling and were randomly divided into family rescyilincy trianing pakage (20 people) cognitive- spiritual hope trianing (20 people) and control (20 people) groupes. The people participating in the research in three stages ansewered to the family rescilince questionnaire (Sixbey, 2005). The collected data were analyzed at two levels of descriptive statistics (mean and standard deviation) and inferential statistics in this study (variance analysis with repeated measurements and Bonferroni post hoc test). It was used for data analysis (by spss software version 24). Results: The data analysis showed that the cognitive-spiritual hope training had a significant effect on family resilience (F= 23.04, P<0.001), and its dimensions, problem solving (F= 23.04 P<0.01), spirituality (F= 21.11 P<0.003), acceptance (F= 10.85 P<0.001), but the family resilience training pakage was also significantly more effective on improving family resilience and had a more significant effect (P< 0.01). Counclusion: According to the findings of the present research, it is possible to use cognitive-spiritual hope training and family resilience training to increase the level of family resilience and its dimensions in kidney patients undergoing hemodialysis.